A study on antimycobacterial activity and phytochemical constituents of Dipterocarpus sublamellatus foxw. hexane extract (DSHE) - Sabran, Siti Fatimah; Mazlun, Muhamad Harith; Abadullah, Zunoliza; Mohamed, Maryati; Abu Bakar, Mohd. Fadzelly; Pa’ee, Furzani; Cuevas Linatoc, Alona (Advanced Scientific Research, 2020)
Purpose: To investigate the antimycobacterial activity and to profile the phytochemicals of Dipterocarpus sublamellatus hexane extract (DSHE). Methodology: Using Mycobacterium smegmatis as a rapid screening model of TB strain, the bacterial cells were treated with 4-fold of Minimum Inhibitory Concentration (MIC=0.78 mg/mL) of DSHE. Significant cellular leakage of DSHE-treated cells were quantified spectrophotometrically at 280 nm. Microscopic study using FE-SEM was employed to indicate any morphological changes induced on bacterial cell shape. Phytochemical profiles of DSHE was conducted using GC-MS analysis. Results: The bacterial cells treated with 4-fold of Minimum Inhibitory Concentration (MIC=0.78 mg/mL) of DSHE rapidly inhibited the bacterial cell growth as early as 8 h of treatment. cell membrane integrity were severely interrupted and losing the vital constituents for cell survival and growth. Substantial morphological changes were induced on bacterial cell shape, supporting the interaction of DSHE with cell wall/membrane of M. smegmatis. GC-MS analysis of DSHE suggested that pyrazole and phenanthroline derivatives were among 23 major phytochemical constituents that potentially contributed to the antimycobacterial activity. Applications/Originality/Value: A further study in this direction potentially leads to the discovery of target-specific antimycobacterial agents and provides a basis that this timber species has to be conserved and managed sustainably.